Incidence and Risk Factors for Infection Following Transcatheter Aortic Valve Implantation. (20th June 2016) - Shi, Yuhao; Wijeysundera, Harindra C.; Fremes, Stephen E.; Simor, Andrew E.
Abstract : We identified risk factors for infection following transcatheter aortic valve implantation (TAVI); infection occurred in 35 (13.8%) of 253 patients. Variables associated with infection included chronic obstructive pulmonary disease (OR, 1.2; 95% CI, 1.1–1.4), postprocedural hemorrhage (OR, 1.2; 95% CI, 1.0–1.3), and procedure-related stroke (OR, 1.6; 95% CI, 1.3–2.1). Infect Control Hosp Epidemiol 2016;37:1094–1097